Pengaruh Konten Media Sosial Line Today Terhadap Minat Baca Remaja Akhir di Kota Bekasi - Stefanus Imanuel; Nani Kurniasari (UNIVERSITAS KALBIS, 2022)
One of the most used social media in Indonesia is Line. Line has feature, named Line Today which provides a variety of news for its users. Indonesian people’s reading interest is also relatively low, especially teenagers. With Line Today that provides various kind of news, researcher wants to find out the effect of Line Today content on teenagers reading interest in Bekasi. This research is conducted using a survey method and an online questionnaire instrument that was created using google form, and distributed to 100 respondents. This study uses Stimulus-Response theory as the foundation of this research. The results of this research is Line Today has an influence on teenagers reading interest in Bekasi by 69,5%. In addition, the level of relationship between two variables is very strong, because the pearson correlation calculation shows the number 0,834. In the t test, ho is rejected and ha is accepted because the t arithmetic is larger than the t table, which is 14,943 > 1,985.